2014
DOI: 10.1248/cpb.c13-00579
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Polysaccharide-Based Transdermal Films for the Controlled Delivery of Nifedipine

Abstract: It was aimed to develop the matrix type polysaccharide-based transdermal films of nifedipine (NFD) to provide its long term plasma concentration. The mechanical tests were carried out on gel formulations which were utilised in the fabrication of transdermal films to determine the type of polymer (pectin, sodium alginate) and plasticizer (propylene glycol, glycerine) as well as their concentrations. The mechanical strength, elasticity, bioadhesiveness and the drug release characteristics of optimised films cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
(53 reference statements)
2
16
0
Order By: Relevance
“…We observed that eucalyptol containing gel formulation G-EU showed the highest elasticity value (0.87 ± 0.05). Bektaş et al, showed that sodium alginate as polymer at concentration of 4.5% and propylene glycol at a concentration of 7.5% as plasticizer were suitable for fabrication of transdermal films of nifedipine [5]. Our results are in accordance with this finding.…”
Section: Code Hardness (N) Elasticity (Mj) Cohesiveness Adhesiveness supporting
confidence: 91%
See 4 more Smart Citations
“…We observed that eucalyptol containing gel formulation G-EU showed the highest elasticity value (0.87 ± 0.05). Bektaş et al, showed that sodium alginate as polymer at concentration of 4.5% and propylene glycol at a concentration of 7.5% as plasticizer were suitable for fabrication of transdermal films of nifedipine [5]. Our results are in accordance with this finding.…”
Section: Code Hardness (N) Elasticity (Mj) Cohesiveness Adhesiveness supporting
confidence: 91%
“…We observed that there was not a significant difference between the gel formulations G-NR, G-EU, G-TP, and G-LM in the mean of cohesiveness (p > 0.05). The cohesiveness of the sodium alginate based gels in our study ranged between 0.85 ± 0.12 and 0.91 ± 0.04 which are in accordance with literature [5].…”
Section: Code Hardness (N) Elasticity (Mj) Cohesiveness Adhesiveness supporting
confidence: 91%
See 3 more Smart Citations